Gallium Nitride Processing for Electronics, Sensors and Spintronics - Pearton, Stephen J.; Abernathy, Cammy R.; Ren, Fan.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2006)
Semiconductor spintronics is expected to lead to a new generation of transistors, lasers and integrated magnetic sensors that can be used to create ultra-low power, high speed memory, logic and photonic devices. Useful spintronic devices will need materials with practical magnetic ordering temperatures and current research points to gallium and aluminium nitride magnetic superconductors as having great potential. Gallium Nitride Processing for Electronics, Sensors and Spintronics details current research into the properties of III-nitride semiconductors and their usefulness in novel devices such as spin-polarized light emitters, spin field effect transistors, integrated sensors and high temperature electronics. Written by three of the world’s leading researchers in nitride semiconductors, the book provides an excellent introduction to gallium nitride technology and will be of interest to all reseachers and industrial practitioners wishing to keep up to date with developments that may lead to the next generation of transistors, lasers and integrated magnetic sensors. The Engineering Materials and Processes series focuses on all forms of materials and the processes used to synthesise and formulate them as they relate to the various engineering disciplines.The series deals with a diverse range of materials: ceramics, metals (ferrous and non-ferrous), semiconductors, composites, polymers biomimetics, etc. Each monograph in the series is written by a specialist and demonstrates how enhancements in materials and the processes associated with them can improve performance in the field of engineering in which they are used.
Advanced Processing of Gallium Nitride for Electronic Devices -- Dry Etching of Gallium Nitride and Related Materials -- Design and Fabrication of Gallium High-Power Rectifiers -- Chemical, Gas, Biological, and Pressure Sensing -- Nitride-Based Spintronics -- Novel Insulators for Gallium Nitride Metal-Oxide Semiconductor Field Effect Transistors and AlGaN-GaN Metal-Oxide Semiconductor High Electron Mobility Transistors.
Keywords: Electronics; Microelectronics; Optical materials; Electronic materials; Nanotechnology; Condensed matter; Electronics and Microelectronics, Instrumentation; Optical and Electronic Materials; Nanotechnology; Condensed Matter Physics